2021
DOI: 10.5817/cp2021-3-6
|View full text |Cite
|
Sign up to set email alerts
|

Social media and eating disorder psychopathology: A systematic review

Abstract: The relationship between socialization through social media (SM) and eating disorders (EDs) is a serious problem for public health, largely affecting the mental health of younger people. This work aimed to identify scientific works addressing ED psychopathologies, studying their relationship with SM usage. In this systematic review, we analyze the available scientific evidence, thereby providing tools for intervention, prevention, and treatment. A systematic review and PRISMA analysis of narrative syntheses wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 80 publications
1
26
0
5
Order By: Relevance
“…[I] try to work out at home but [it's] not the same feeling". It is already known that social media plays a large part in shaping and predicting ED behaviours [33,34] due to their tendency to promote social comparison [35], particularly content that focused on "fitspiration" [36]. Within the context of COVID-19, it was found that exposure to fitness-related content on social media led to greater appearance anxiety during this period [37], thereby corroborating the present study findings.…”
Section: Influences Of Social Mediasupporting
confidence: 89%
“…[I] try to work out at home but [it's] not the same feeling". It is already known that social media plays a large part in shaping and predicting ED behaviours [33,34] due to their tendency to promote social comparison [35], particularly content that focused on "fitspiration" [36]. Within the context of COVID-19, it was found that exposure to fitness-related content on social media led to greater appearance anxiety during this period [37], thereby corroborating the present study findings.…”
Section: Influences Of Social Mediasupporting
confidence: 89%
“…Such negative feeling and discomfort is socioculturally driven and adversely affects individuals’ well-being and mental health. These negative emotions also interweave with distorted cognition that influences peoples’ understanding and attitudes toward appropriate exercise, eating behaviors, and body image (Bowles et al, 2021; Padín et al, 2021; Rounds & Stutts, 2020).…”
Section: Fitspiration-associated Risksmentioning
confidence: 99%
“…Multiple researchers have found that patients' attention to the display of body imagery on social media plays a significant role in leading to the will or idea of an alternated diet plan, thus triggering long-term mishandling of nutrients and energy intake [6]. Several issues and consequences are caused by long-term attention to the imagery or videos showing body imagery.…”
Section: Social Mediamentioning
confidence: 99%